2016
DOI: 10.1136/bjophthalmol-2016-308534
|View full text |Cite
|
Sign up to set email alerts
|

Are all children with visual impairment known to the eye clinic?

Abstract: The study demonstrates significant unmet need or undiagnosed visual impairment in a high-risk population. It also highlights the poor uptake of hospital eye care for children identified with significant visual needs and suggests the importance of providing in-school assessment and support, including refractive correction, to fully realise the benefits of a visual assessment programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 7 publications
(12 reference statements)
2
16
0
Order By: Relevance
“…This is considerably lower than headline rates of cooperation reported by other studies [2,4,5]. Pilling [4] reported a rate of 97% cooperation with functional vision assessment which included the use of the Bradford box, a novel visual function instrument [18]. The rate of cooperation with standard tests (Crowded Keeler LogMAR, Crowded Kays pictures and Cardiff Acuity Test) was 62%, a similar proportion to that found in our evaluation.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…This is considerably lower than headline rates of cooperation reported by other studies [2,4,5]. Pilling [4] reported a rate of 97% cooperation with functional vision assessment which included the use of the Bradford box, a novel visual function instrument [18]. The rate of cooperation with standard tests (Crowded Keeler LogMAR, Crowded Kays pictures and Cardiff Acuity Test) was 62%, a similar proportion to that found in our evaluation.…”
Section: Discussionsupporting
confidence: 74%
“…Despite the availability of a wide range of visual acuity tests, a reliable measurement of visual acuity using established methods was only possible for 60.5% of children. This is considerably lower than headline rates of cooperation reported by other studies [2,4,5]. Pilling [4] reported a rate of 97% cooperation with functional vision assessment which included the use of the Bradford box, a novel visual function instrument [18].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“… 4 Certification takes place within Eye clinics and there is evidence of poor uptake of hospital eye care for children with significant visual needs. 10 …”
Section: Discussionmentioning
confidence: 99%
“…This creates a compounding burden on already strained NHS services by increasing clinic waiting times and reducing the number of appointments available for new patients. Furthermore, it has been shown that children have a high 'did not attend (DNA)' rate at hospital clinics [21,22]. Provision of eyecare in-school allows for another child to be examined in lieu of any absentees, reducing the financial impact of missed appointments [23].…”
Section: In-school Servicementioning
confidence: 99%